Exploring New Territories - Vervarcke, Anne (Homœopathic Links, 2015)
In this article, the author investigates reasons for the unstoppable decline of homeopathy in the West. She argues that old homeopathy in a world that has changed might not meet the need of the ‘new patients’ any longer. Homeopathy has to move forwards, balancing reason with intuition and mind with heart. Homeopathy essentially is an initiation process into becoming a healer. We already have arrived in the pioneering stage and are exploring new territories.
Keywords: Homeopathy in decline; Homeopathy for the soul; Initiation process; New homeopathy; Intuition; Pioneering